The Level of Understanding and Strategies to Enhance Financial Literacy among Malaysian - Murugiah, Logasvathi (International Journal of Economics and Financial Issues, 2016)
Financial world is crucial as people assume more responsibility for their own financial security. For that reason, financial literacy play a critical role in helping individual to manage their money wisely. Moreover, the needs to study into a national wide strategy to enhance Malaysians personal financial literacy and improve the necessary abilities to keep their personal financial health in the proper insightful are significantly important. Hence, the objectives of this paper is to identify the understanding level of financial literacy in Malaysia and strategies to enhance financial literacy level among Malaysian. Qquestionnaires were distributed to 2500 Malaysian in Peninsular Malaysia, age ranging from 18 to 45 years old in 2014. The survey shows that Malaysian consider themselves good in financial literacy but in reality they are still weak in mastering financial literacy knowledge. This study also shows that, in Malaysia context, financial literacy among young men who earn below RM1500 and certificate qualification holders need to be targeted as focus group to increase their financial literacy awareness and financial knowledge. Therefore, strategies to create awareness and improve financial literacy knowledge among Malaysian has been identified in this study. Moreover, a good knowledge in financial literacy will make an important contribution to the soundness and efficiency of the financial system and to the performance of the country's economy. Keywords: Financial literacy, Financial education, Strategies and Malaysia. JEL Classifications: D14, D18, D31, D83, D91